Learning and teaching academic standards project : Engineering and ICT : learning and teaching standards statement. - Wright, Sue M.; Hadgraft, Roger; Cameron, Ian. (Australian Learning and Teaching Council, 2010)
The Learning and Teaching Academic Standards Statement for Engineering and ICT is intended to offer a succinct description of the nature and extent of the discipline and to distinguish the threshold, ie minimum, level of achievement that can be expected of an Australian bachelor level graduate with a major in Engineering and ICT. The statement also sets out careers Engineering and ICT graduates might pursue